2019
DOI: 10.1177/0741713619858131
|View full text |Cite
|
Sign up to set email alerts
|

Including Critical Whiteness Studies in the Critical Human Resource Development Family: A Proposed Theoretical Framework

Abstract: While the human resource development (HRD) literature has made strides to incorporate critical race theory, critical Whiteness studies has not been substantively addressed. White experiences need to be incorporated into organizational learning literature in racialized ways. Unpacking the racialized experiences of Whites in organizational settings is important because it challenges the often-unstated assumption that White experiences are normal and neutral. The uncritical centering of Whiteness is part of what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…Several actions were suggested that could be useful in forwarding the cause of social justice in HRD. These included questioning power relations and the taken‐for‐granted, involving multiple stakeholders, redressing historical inequity, working with marginalized peoples, embracing diverse ways of knowing, reducing barriers, enhancing reflexivity, and challenging commodification of employees (Bierema, ; Bohonos, ; Byrd, ; Collins, ; Stanley, ).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several actions were suggested that could be useful in forwarding the cause of social justice in HRD. These included questioning power relations and the taken‐for‐granted, involving multiple stakeholders, redressing historical inequity, working with marginalized peoples, embracing diverse ways of knowing, reducing barriers, enhancing reflexivity, and challenging commodification of employees (Bierema, ; Bohonos, ; Byrd, ; Collins, ; Stanley, ).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This in turn reduces the likelihood that the organization will enact policies that are harmful to historically marginalized peoples. In order to truly honor the voices of minoritized peoples, organizations must embrace diverse ways of knowing and recognize that the majority group's ways of knowing tend to favor members of that group (Bierema, ; Bohonos, ; Collins, ; Stanley, ). Implicit and unconscious bias seep into everyday, mundane acts that have large‐scale impact.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…As a result, settler-colonialism gave birth to various policies and practices that have led to the oppression and marginalization of Indigenous peoples during post-contact (Marom, 2019, p.322). These policies and practices are evident throughout Canadian history and are created and maintained through immigration and migration laws to create a "white" North America (Baffoe et al, 2014;Bohonos, 2019;Nayak, 2007). However, Nayak (2007) and Ambrosio (2014) argue that the effects of whiteness has been, and still is, detrimental to white bodies.…”
Section: Roots To Colonialismmentioning
confidence: 99%
“…Anderson (2015) argued that Black people often perceive themselves as unwelcome in overwhelmingly White spaces, and that access to vital resources — including employment (Bohonos & Duff, in press; Carbado & Gulati, 2013) — frequently requires POC to enter White spaces where humiliation and hostility are normative. Literature exploring White privilege (Bohonos, 2019a; DiAngelo, 2018; Macintosh, 1997) further emphasizes the ways that White people benefit from systemic and interpersonal manifestations of racism. Macintosh (1997) offered the following definition:
White privilege is like an invisible weightless knapsack of special provisions, assurances, tools, maps, guides, codebooks, passports, visas, clothes, compass, emergency gear, and blank checks.
…”
Section: Studying White Working‐class Men Through Critical Race Theormentioning
confidence: 99%